Clinical Relevance of Informal Coercion in Psychiatric Treatment—A Systematic Review - Hotzy, Florian; Jaeger, Matthias (Frontiers in Psychiatry, 2016)
Introduction: Although informal coercion is frequently applied in psychiatry its use is discussed controversially. This systematic review aimed to summarize literature on attitudes towards informal coercion, its prevalence and clinical effects. Methods: A systematic search of Pubmed, Embase, PsycINF and Google Scholar was conducted. Publications were included if they reported original data describing patients’ and clinicians’ attitudes towards and prevalence rates or clinical effects of informal coercion. Results: 21 publications out of a total of 162 articles met the inclusion criteria. Most publications focused on leverage and inducements rather than persuasion and threat. Prevalence rates of informal coercion were 29 to 59%, comparable on different study sites and in different settings. The majority of mental health professionals as well as one to two thirds of the psychiatric patients had positive attitudes, even if there was personal experience of informal coercion. We found no study evaluating the clinical effect of informal coercion in an experimental study design. Discussion: Cultural and ethical aspects are associated with the attitudes and prevalence rates. The clinical effect of informal coercion remains unclear and further studies are needed to evaluate these interventions and the effect on therapeutic relationship and clinical outcome. It can be hypothesized that informal coercion may lead to better adherence and clinical outcome but also to strains in the therapeutic relationship. It is recommendable to establish structured education about informal coercion and sensitize mental health professionals for its potential for adverse effects in clinical routine practice.